2019
DOI: 10.12927/hcpol.2019.26072
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning Implementation of a Personalized Approach in Breast Cancer Screening Programs: Stakeholder Perspectives

Abstract: Background: Advances in genomics and epidemiology can foster the implementation of a riskbased approach to current age-based breast cancer screening programs. This personalized approach would challenge the trajectory for women in the healthcare system by adding both a risk-assessment step (including a genomic test) and screening options. Objective: The aim of this study is to explore, from an organizational perspective, the acceptability of different proposals for each step of the trajectory for women in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Nursing staff were underrepresented in the included studies. Decision makers have suggested that nurses could assume increased duties in risk assessment and management to support implementation of risk-based screening and prevention [71]. In relation to primary prevention, general practitioners have been found to perceive intervening on obesity as an inappropriate use of their time in comparison to nurses who report feeling responsible for raising the topic [72].…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…Nursing staff were underrepresented in the included studies. Decision makers have suggested that nurses could assume increased duties in risk assessment and management to support implementation of risk-based screening and prevention [71]. In relation to primary prevention, general practitioners have been found to perceive intervening on obesity as an inappropriate use of their time in comparison to nurses who report feeling responsible for raising the topic [72].…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…Building on the results from our previous engagement with decision makers [60][61][62], and our extensive research on genetic discrimination [63] and regulatory approval in personalized healthcare [64], potential options to address emergent socio-ethical and legal challenges associated with the implementation of risk-based screening have been identified. These options are being investigated through interdisciplinary legal, ethical and social analyses described below.…”
Section: Socio-ethical and Legal Issuesmentioning
confidence: 99%
“…As the personalized risk-based approach may involve risk estimation for tens of thousands of women each year, we anticipate that specialized medical health professionals (e.g., geneticists, genetic counsellors) may be reserved for the most complex cases. Decision makers have suggested that nurses could assume increased duties [62], including sampling, requesting laboratory analysis, ordering imaging exams, and providing personalized follow-up recommendations to support this approach. Consideration of this approach is critical both to containing costs and avoiding resource constraints (e.g., genetic counsellors).…”
Section: Socio-ethical and Legal Issuesmentioning
confidence: 99%
“…In the search for efficiency and risk reduction for health service users, ways to institute care centered on their needs and supported by evidence are currently being discussed, including for breast cancer detection programs (10)(11)(12)(13)(14)(15)(16) . Thus, modeling, protocols, tools and feasibility assessments emerged for the implementation of personalized breast cancer prevention and early detection by risk stratification, involving users and other health system actors (5,(10)(11)(12)(13)(14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%